Underground investigation of extensive air showers spectra at high energy range of cosmic rays and other research in the Pyhäsalmi mine - Yerezhep, N.; Trzaska, W.H.; Bezrukov, L.; Enqvist, T.; Kuusiniemi, P.; Inzhechik, L.; Joutsenvaara, J.; Loo, K.; Lubsandorzhiev, B.; Slupecki, M.; Saduyev, N.O.; Baktoraz, A.; et al. (Recent Contributions to Physics, 2020)
High energy particles reaching the Earth’s atmosphere are known as cosmic rays. As a result of interactions with nuclei of air molecules, cosmic rays induce showers of secondary particles, which can be divided into 3 components: electromagnetic, hadronic and muonic components. The Experiment with Multi Muon Array (EMMA), located at the depth of 75 m in the Pyhäsalmi mine in Finland, investigates the muonic component of the Extensive Air Showers (EAS) to deduce the direction, energy, and the mass of the primary cosmic ray particles. In this paper we give a concise description and methodology used by EMMA followed by a brief review of the C14 experiment. Finally, we review the feasibility to host in the Pyhäsalmi mine a future large-scale liquid-based neutrino detector and implement a novel concept of acoustic detection of neutrinos in bedrock utilizing the network of many kilometers of boreholes surrounding the now-exploited ore body.